Creation of an iPSC-Based Skeletal Muscle Model of McArdle Disease Harbouring the Mutation c.2392T>C (p.Trp798Arg) in the PYGM Gene - Victoria Cerrada; Inés García-Consuegra; Joaquín Arenas; M. Esther Gallardo (Biomedicines, 2023)
McArdle disease is a rare autosomal recessive condition caused by mutations in the PYGM gene. This gene encodes the skeletal muscle isoform of glycogen phosphorylase or myophosphorylase. Patients with McArdle disease have an inability to obtain energy from their muscle glycogen stores, which manifests as a marked exercise intolerance. Nowadays, there is no cure for this disorder and recommendations are intended to prevent and mitigate symptoms. There is great heterogeneity among the pathogenic variants found in the PYGM gene, and there is no obvious correlation between genotypes and phenotypes. Here, we present the generation of the first human iPSC-based skeletal muscle model harbouring the second most frequent mutation in PYGM in the Spanish population: NM_005609.4: c.2392T>C (p.Trp798Arg). To this end, iPSCs derived from a McArdle patient and a healthy control were both successfully differentiated into skeletal muscle cells using a small molecule-based protocol. The created McArdle skeletal muscle model was validated by confirming distinctive biochemical aspects of the disease such as the absence of myophosphorylase, the most typical biochemical feature of these patients. This model will be very valuable for use in future high-throughput pharmacological screenings.